“É preciso educar as meninas”: história e memória institucional do Patronato Coração Imaculado de Maria em São Bernardo das Russas - CE (1937-1953) - Lima, Carlos Rochester Ferreira de (2020)
This research aims to understand the educational processes aimed at for the formation of girls and young women in the countryside of Ceará, from the analysis of history and institutional memory of the first school to teach girls in the Vale do Jaguaribe region, the Patronato Coração Imaculado de Maria. This school was composed by the Patronato, for students from wealthy families, and the Sagrado Coração de Jesus School, for students who studied for free, from poor families. The construction, and start-up of this school, dates back to the period of disputes between the cities of Limoeiro do Norte and Russas over the bishopric’s headquarters, and it is one of our goals to describe, biographically, the characters who helped write the history and the memory of Patronato Coração Imaculado de Maria. In order to better understanding this period, we make, in this paper, a historical narrative of the socio-political-economic situation in Brazil between 1937 and 1953, it being necessary to describe important facts from before this period, taking into account the matters of moral values guided by the alliance between the State and the Church, education was permeated by impositions and limitations, especially concerning the education of women, which is the main objective of this work. We based ourselves theoretically and methodologically on the History of Comparative Education, as na attempt to visualize, from a chronological perspective, the insertion of Russas and Ceará girls in the environments of formal instruction. Hemerographic sources were used through newspapers produced in Ceará, in Vale do Jaguaribe and in Russas, which span the years studied in this work. We also made use of the monthly minutes produced by the nuns responsible for Patronato’s education since the year of its foundation, and these documents act as rules manuals of what was allowed, or not, to be done at school and remains as a living memory of the institution. In pursuit of our goals, we heard reports from alumni, nuns and school staff to reveal, from a historical perspective, the students’ daily life, taking into account the contradictions that exist in a female school for a twentieth-century woman project. We believe that the related story will be very useful for us to understand the changes and permanences regarding access to education, social visibility and their experiences in this space of Instruction.